EDUKASI PERAWATAN LUKA MENGGUNAKAN METODE MOIST WOUND HEALING TERHADAP GANGGUAN INTEGRITAS KULIT PADA WARGA RT 02 DUSUN BAMBARABA DESA GUNUNG SARI - Allan, Viere Allanled Siauta; Djuwartini; Elifa Ihda Rahmayanti; Ardianti; Bahira; Winda Kristin; Wanda Febrianti; Yuni Setiani Salakea; Yenuarti Nunik; Andi Putri Ayu; Anisa Rihan Fadilah; Moh Rendi (LPPM UNINUS, 2024)
The moist wound healing method is a method of wound care to keeps the wound moist and dries quickly. The method that uses pre-experimental design with one group pretest-posttest. The aim of the activity is to provide education to public about wound care using the moist wound healing method. The results of this activity that there an increase in level of knowledge in 30 respondents. Before education provided, respondents who had a good level of knowledge were 3 respondents and after the education provided knowledge of respondents increased to 22 respondents. While the respondents with a low level of knowledge before the education provided were 14 and after that decreased to 2 respondents. It is hope the local health service center will continue to provide regular education to increase knowledge and public health status. Keywords : wound care, moist wound healing